Introducing the women's Hebrew Bible - Scholz, Susanne (Introductions in Feminist Theology, 2014)
This book introduces readers to the diverse field of feminist studies on the Hebrew Bible. Not organized as a traditional introduction to the ""Old Testament,"" the manuscript does not follow a biblical book-by-book structure, but provides an introductory survey of the history and issues as they relate to feminist readings and readers of the Hebrew Bible. Accordingly, feminist scholars of the Bible, their career struggles, and biblical texts, characters, and themes stand in the forefront of this introduction. The volume is biased toward ""Western"" feminist scholarship because of the historica